Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


The Brainliest Answer!
This question is based on the formula (x-1)(x+1)=x²-1. Now starting from the last product, 2011*2013=(2012-1)(2012+1)=2012²-1. Now, √{1+2012²-1}=2012. Next product 2010*2012=2011²-1. Therefore, √{1+2011²-1}=2011. Going on like this you get the answer to be 2009
2 5 2
ok thnx i got it
Happy to help
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts